Computational Study of Allotropic Structures of Carbon by Density Functional Theory (DTF) - J. M. González (Ingeniería y Ciencia, 2014)
In this paper using Density Functional Theory (DFT), the principal carbon allotropic crystalline structures (Diamond, graphite, nanotube y fullerene- C60) were simulated. The results showsdiamond sp3 bonds formation be- tween carbon atomsand low reactivity, indicating low probability of lateral compound formation and high mechanical properties. Interplanar weak- ness was evidentin graphite structure, which is related to solid lubrication process.Carbon-Carbon metallic bonds and polarizations at the edges of the structure were observed in Armchair Carbon Nanotube, stabilizing the systemwhich allowsthe nanotube continuous growth. In fullerene C60 structureaFaraday nano-gauge behavior was confirmed, together withlow probability of interatomic polarization, indicating high structural stability. Besides Total Energy (TE) and Nuclear Repulsion Energy (NRE) values were used to perform energetic comparisons between different structures, allowing the study of electronic stability and their relationship to mechanical properties.